Pengembangan Media Jigsaw Puzzle Pendidikan Pancasila Berbasis Model Cooperative Learning Tipe Student Team Achievement Division di Sekolah Dasar - Ranti Satriani Putri; Muhammad Fachri Adnan; Muhammadi Muhammadi; Mutiara Felicita Amsal (Universitas Negeri Padang, 2025)
This research was motivated by students' lack of understanding of Pancasila Education learning materials due to the lack of engaging and interactive learning media, which leads to boredom, inactivity, and low learning outcomes. Therefore, interactive and educational learning media are needed to improve cognitive abilities and student engagement. The objective of this research was to develop a jigsaw puzzle media based on the STAD model that is valid, practical, and effective for Pancasila Education learning in fourth-grade elementary schools. This research employed a research and development (R&D) method using the ADDIE model, which consists of the following stages: Analysis, Design, Development, Implementation, and Evaluation. The instruments used to collect data for this development included a validity instrument, a practicality instrument, and an effectiveness instrument. The validity test results from the three validator experts were categorized as